Reheating and dark matter freeze-in in the Higgs-R 2 inflation model - Shuntaro Aoki; Hyun Min Lee; Adriana G. Menkara; Kimiko Yamashita (Journal of High Energy Physics, 2022)
Abstract We study the post-inflationary dynamics for reheating and freeze-in dark matter in the Higgs-R 2 inflation model. Taking the perturbative approach for reheating, we determine the evolution of the temperature for radiation bath produced during reheating and determine the maximum and reheating temperatures of the Universe. Adopting a singlet scalar dark matter with a conformal non-minimal coupling and a vanishing Higgs-portal coupling, we discuss the freeze-in production of dark matter both from the non-thermal scattering during reheating and the thermal scattering after reheating. We find that thermal scattering is dominant for dark matter production in our model due to the high reheating temperature. The reheating temperature in our model is determined dominantly by the Higgs condensate to be up to about 1014 GeV and dark matter with masses up to about 109 GeV can be produced with a correct relic density.